Small molecule activation of NOTCH signaling inhibits acute myeloid leukemia - Ye, Qi (Sci Rep, 2016)
Aberrant activation of the NOTCH signaling pathway is crucial for the onset and progression of T cell leukemia. Yet recent studies also suggest a tumor suppressive role of NOTCH signaling in acute myeloid leukemia (AML) and reactivation of this pathway offers an attractive opportunity for anti-AML therapies. N-methylhemeanthidine chloride (NMHC) is a novel Amaryllidaceae alkaloid that we previously isolated from Zephyranthes candida, exhibiting inhibitory activities in a variety of cancer cells, particularly those from AML. Here, we report NMHC not only selectively inhibits AML cell proliferation in vitro but also hampers tumor development in a human AML xenograft model. Genome-wide gene expression profiling reveals that NMHC activates the NOTCH signaling. Combination of NMHC and recombinant human NOTCH ligand DLL4 achieves a remarkable synergistic effect on NOTCH activation. Moreover, pre-inhibition of NOTCH by overexpression of dominant negative MAML alleviates NMHC-mediated cytotoxicity in AML. Further mechanistic analysis using structure-based molecular modeling as well as biochemical assays demonstrates that NMHC docks in the hydrophobic cavity within the NOTCH1 negative regulatory region (NRR), thus promoting NOTCH1 proteolytic cleavage. Our findings thus establish NMHC as a potential NOTCH agonist that holds great promises for future development as a novel agent beneficial to patients with AML.